IMPLEMENTASI PERATURAN GUBERNUR NOMOR 31 TAHUN 2008 TENTANG KETENTUAN PENGISIAN DAFTAR HADIR BAGI PEGAWAI NEGERI SIPIL DI LINGKUNGAN KERJA DINAS PETERNAKAN PROVINSI KALIMANTAN TIMUR - Sukamto Dwi Cahyono (Jurnal Paradigma (JP), 2017)
The aim of this study is to describe and analyze the implementation of the Governor Regulation No. 31 of 2008 on Provision Charging Attendance for the civil servants in the Work Environment East Kalimantan Provincial Livestock Office. Sources of data taken from the informant and key informants and supported by secondary data analysis of the data used is dikem-interactive model were developed by Milles, Huberman and Saldana (2014: 33) through the stages.